Vegetarianism and child growth: Within-district evidence from the 2015-2016 Indian national family health survey (P10-032-19) - Palloni, Giordano; Headey, Derek D. (Oxford University Press, 2019)
Most research on stunting in India ignores the role of diets, including the unusually high prevalence of lacto-vegetarianism (LVG). LVG is a concern in India because nutrient-dense animal-sourced foods (ASFs) are highly recommended in early childhood. We therefore explore how parental LVG is associated with linear growth and child dietary patterns in India.